Comparison of laminoplasty versus laminectomy and fusion in the treatment of multilevel cervical ossification of the posterior longitudinal ligament: A systematic review and meta-analysis. Issue 29 (July 2018) - Ma, Lei; Liu, Feng-Yu; Huo, Li-Shuang; Zhao, Zheng-Qi; Sun, Xian-Ze; Li, Feng; Ding, Wen-Yuan
Abstract: Background: Laminoplasty (LP) and laminectomy with fusion (LF) were recognized as two reliable and effective way in treating multilevel cervical ossification of the posterior longitudinal ligament (OPLL). However, there was no clear conclusion on which method is better. A meta-analysis was conducted to evaluate the clinical results between LP and LF in the treatment of multilevel cervical OPLL. Methods: An extensive search of literature was performed in PubMed, Embase, the Cochrane library, CNKI (Chinese database), and WANFANG (Chinese database). The following outcomes were extracted: the Japanese Orthopedic Association (JOA) scores, visual analog scale (VAS), cervical lordosis, cervical range of motion (ROM), complications, blood loss, and operation time. Data analysis was conducted with RevMan 5.3. Results: A total of 11 studies were included in the final analysis. The results indicated that no significant differences between LP and LF group in terms of preoperative JOA scores ( P  = .58), postoperative JOA scores ( P  = .60), JOA scores improvement rate ( P  = 0.64), preoperative VAS ( P  = .34), postoperative VAS (P=.20), preoperative range of motion (ROM) ( P  = .10), postoperative ROM ( P  = .18), preoperative cervical lordosis ( P  = .56), C5 palsy ( P  = .16), and axial pain ( P  = .21). LF group showed larger postoperative cervical lordosis than LP group [standardized mean difference (SMD) = 1.13 (2.03, 0.24), P  = .01]. However, LP group showed lower operation time [mean difference (MD) = 19.42 (26.87, 11.97), P  < .001] and blood loss [MD = 94.78 (179.05, 10.51), P  = .03] than LF group. Conclusion: Both LP and LF can achieve clinical improvement in the treatment of multilevel cervical OPLL. LF was superior to LP in maintaining cervical lordosis. However, LP showed lower surgical trauma than LF. Kyphosis line (K-line) may be a good criterion in the selection of posterior surgery. LP was performed for the patients with K-line (+) and LF for K-line (−).